The Role of Islamic Education Teachers in Improving Students Abilities Reciting Al-Quran - Zanjabila, Muhammad Rizal; M.S, Lintang Hikmah; Kharisma, Refi; Hunaida, Wiwin Luqna; Huda, Sholikul (The Magister of Islamic Education IAIN Pontianak, 2023)
This article explains the role of Islamic religious education teachers to improve students' ability to read the Quran. The main objective of this study was to evaluate the impact of PAI learning on improving the ability to read the Quran in grade IX students at SMPN 1 Jombang. This research uses a qualitative approach and descriptive type with a case study method. The main data sources in this study are Islamic religious education teachers and students. Data collection techniques use interviews and observation. The results showed a significant increase in the ability to read the Quran in students, this is inseparable from the role of Islamic Religious Education teachers in designing relevant learning, namely using learning strategies that are directly related to the Quran which includes choosing verses that are in accordance with the learning material, ensure the text of the Quran is studied according to the student's level of understanding, and create relevant connections between the teaching material and its application in everyday life.